The contribution of each anterior cruciate ligament bundle to the Lachman test A CADAVER INVESTIGATION - (:unkn) unknown (BRITISH EDITORIAL SOC BONE JOINT SURGERY, 2012)
The clinical diagnosis of a partial tear of the anterior cruciate ligament (ACL) is still subject to debate. Little is known about the contribution of each ACL bundle during the Lachman test. We investigated this using six fresh-frozen cadaveric lower limbs. Screws were placed in the femora and tibiae as fixed landmarks for digitisation of the bone positions. The femur was secured horizontally in a clamp. A metal hook was screwed to the tibial tubercle and used to apply a load of 150 N directed anteroposteriorly to the tibia to simulate the Lachman test. The knees then received constant axial compression and 3D knee kinematic data were collected by digitising the screw head positions in 30 degrees flexion under each test condition. Measurements of tibial translation and rotation were made, first with the ACL intact, then after sequential cutting of the ACL bundles, and finally after complete division of the ACL. Two-way analysis of variance analysis was performed. During the Lachman test, in all knees and in all test conditions, lateral tibial translation exceeded that on the medial side. With an intact ACL, both anterior and lateral tibial landmarks translated significantly more than those on the medial side (p < 0.001). With sequential division of the ACL bundles, selective cutting of the posterolateral bundle (PLB) did not increase translation of any landmark compared with when the ACL remained intact. Cutting the anteromedial bundle (AMB) resulted in an increased anterior translation of all landmarks. Compared to the intact ACL, when the ACL was fully transected a significant increase in anterior translation of all landmarks occurred (p < 0.001). However, anterior tibial translation was almost identical after AMB or complete ACL division. We found that the AMB confers its most significant contribution to tibial translation during the Lachman test, whereas the PLB has a negligible effect on anterior translation. Section of the PLB had a greater effect on increasing the internal rotation of the tibia than the AMB. However, its contribution of a mean of 2.8 degrees amplitude remains low. The clinical relevance of our investigation suggests that, based on anterior tibial translation only, one cannot distinguish between a full ACL and an isolated AMB tear. Isolated PLB tears cannot be detected solely by the Lachman test, as this bundle probably contributes more resistance to the pivot shift.
Keywords: IN-SITU FORCES; ARTHROSCOPIC RECONSTRUCTION; TIBIAL DISPLACEMENT; POSTERIOR MOTION; KNEE STABILITY; PARTIAL TEARS; DIAGNOSIS; DEFICIENCY; STRAIN; TENDON